From Thirst to Thrombosis? Effects of Preoperative Fasting Regimens on Coagulation in Benign Prostatic Hyperplasia Assessed by Low-Frequency Piezoelectric Thromboelastography - Tarabrin, O.; Suslov, O.; Sukhonos, R.; Buhayenko, Ye.; Hladkykh, I.; Kirpichnikova, K. (Journal of Education, Health and Sport, 2025)
Background. Benign prostatic hyperplasia (BPH) is one of the most common urological diseases in elderly men and frequently requires invasive diagnostic procedures. In Ukraine, preoperative preparation traditionally relies on prolonged fasting according to the nil per os (NPO) principle for ≥12 hours, despite contemporary European and American guidelines that allow clear fluids up to 2 hours before anaesthesia [1–3]. Prolonged preoperative water deprivation may promote haemoconcentration, hypercoagulability and an increased risk of thromboembolic complications, which is particularly relevant in elderly BPH patients. Objective. To assess the impact of water deprivation on haemostatic function in elderly patients with BPH by comparing low-frequency piezoelectric thromboelastography (LF-PETEG) parameters in groups with liberal clear-fluid intake versus prolonged NPO in the preoperative period. Materials and Methods. This prospective randomized study included 64 patients aged ≥70 years with confirmed BPH who underwent transrectal ultrasound-guided prostate biopsy between September 2018 and September 2019. None of the patients received antithrombotic or anticoagulant therapy. Haemostasis was assessed by LF-PETEG twice: at admission and 1 ± 0.43 hours before surgery. Patients were randomized into two groups: Group A (n=31) — allowed to drink clear fluids (100–300 mL) up to 2 hours before the procedure; Group B (n=33) — maintained on NPO for 12 ± 2.3 hours before anaesthesia. The following LF-PETEG parameters were analysed: intensity of contact coagulation (ICC), intensity of coagulation drive (ICD), maximum clot density (MA) and index of retraction and clot lysis (IRCL), expressed as percentage relative to normal values. Results. At admission, all patients showed moderate increases in coagulation activity and fibrinolysis: ICC +13.13 ± 8.56%, ICD +22.43 ± 10.93%, MA +44.11 ± 19.31%, IRCL +61.18 ± 31.18% above normal. In Group A, preoperative LF-PETEG parameters remained relatively stable: ICC +12.13 ± 6.11%, ICD +18.87 ± 5.04%, MA +43.51 ± 18.81%, IRCL +64.02 ± 26.22% above normal. In Group B, all parameters increased further: ICC +26.01 ± 7.21%, ICD +39.67 ± 13.57%, MA +64.07 ± 21.81%, IRCL +76.88 ± 42.97% above normal, indicating enhanced hypercoagulability and fibrinolytic activity against the background of prolonged NPO. Conclusions. Elderly BPH patients demonstrate a baseline tendency towards hypercoagulability and increased fibrinolytic activity by LF-PETEG already at admission. Prolonged preoperative water deprivation (NPO 12 ± 2.3 h) leads to additional intensification of these changes, whereas allowing clear fluids up to 2 hours before surgery helps stabilise haemostatic parameters. Optimisation of preoperative fluid intake should be considered an important component of strategies aimed at reducing thrombotic risk in elderly patients with BPH.